Monte Carlo Simulation in Statistical Physics An Introduction - Binder, Kurt.; Heermann, Dieter W.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
Monte Carlo Simulation in Statistical Physics deals with the computer simulation of many-body systems in condensed-matter physics and related fields of physics, chemistry and beyond, to traffic flows, stock market fluctuations, etc.). Using random numbers generated by a computer, probability distributions are calculated, allowing the estimation of the thermodynamic properties of various systems. This book describes the theoretical background to several variants of these Monte Carlo methods and gives a systematic presentation from which newcomers can learn to perform such simulations and to analyze their results. The fifth edition covers Classical as well as Quantum Monte Carlo methods. Furthermore a new chapter on the sampling of free-energy landscapes has been added. To help students in their work a special web server has been installed to host programs and discussion groups (http://wwwcp.tphys.uni-heidelberg.de). Prof. Binder was awarded the Berni J. Alder CECAM Award for Computational Physics 2001 as well as the Boltzmann Medal in 2007. .
Introduction: Purpose and Scope of This Volume, and Some General Comments -- Theoretical Foundations of the Monte Carlo Method and Its Applications in Statistical Physics -- Guide to Practical Work with the Monte Carlo Method -- Some Important Recent Developments of the Monte Carlo Methodology -- Quantum Monte Carlo Simulations: An Introduction -- Monte Carlo Methods for the Sampling of Free Energy Landscapes.
Keywords: Physics; Physical chemistry; Computer simulation; Operations research; Management science; Condensed matter; Statistical physics; Dynamical systems; Physics; Statistical Physics, Dynamical Systems and Complexity; Operations Research, Management Science; Simulation and Modeling; Mathematical Methods in Physics; Condensed Matter Physics; Physical Chemistry; Electronic books